Long-acting injectable antipsychotics for the treatment of bipolar disorder: evidence from mirror-image studies - Francesco Bartoli; Daniele Cavaleri; Christian Nasti; Dario Palpella; Pierluca Guzzi; Ilaria Riboldi; Cristina Crocamo; Sofia Pappa; Giuseppe Carrà (SAGE Publishing, 2023)
Clinical trials and real-world data have shown that long-acting injectable antipsychotics (LAIs) might be an effective therapeutic option also for people with bipolar disorder (BD). However, complementing evidence from mirror-image studies investigating LAIs in BD is scattered and has not been systematically evaluated so far. We thus performed a review of observational mirror-image studies testing the effectiveness of LAI treatment on clinical outcomes in people with BD. Embase, MEDLINE, and PsycInfo electronic databases were systematically searched (via Ovid) up to November 2022. We included six mirror-image studies that compared relevant clinical outcomes between the 12-months after (post-treatment period) and the 12-months before (pre-treatment period) the initiation of a LAI treatment in adults with BD. We found that LAI treatment is associated with a significant reduction in days spent in hospital and number of hospitalizations. Moreover, LAI treatment seems to be associated with a significant decrease in the proportion of individuals with at least one hospital admission, even though data on this outcome were reported by just two studies. In addition, studies consistently estimated a significant reduction of hypo-/manic relapses after LAI treatment initiation, while the effect of LAIs for depressive episodes is less clear. Finally, LAI treatment initiation was associated with a lower number of emergency department visits in the year after LAI initiation. The findings of this review seem to suggest that the use of LAIs is an effective strategy to improve major clinical outcomes in people with BD. Nonetheless, additional research, based on standardized assessments of prevalent polarity and relapses, is needed to identify the clinical characteristics of individuals with BD who are most likely to benefit from a LAI treatment.